Dynamic investigations on cationic dye desorption from chemically modified lignocellulosic material using a low-cost eluent: Dye recovery and anodic oxidation efficiencies of the desorbed solutions. (10th November 2018) - Azzaz, Ahmed Amine; Jellali, Salah; Akrout, Hanene; Assadi, Aymen Amine; Bousselmi, Latifa
Abstract: One of the main challenges of dyes adsorption technology application wide-spreading is the fate of the generated dyes-loaded-biomasses, which in certain cases could represent a serious threat to the environment. In this research work, an innovative and eco-friendly approach was established for the management of a lignocellulosic material (alkaline treated orange tree sawdust: ATOS) loaded with methylene blue (MB) at a concentration of 107 mg g −1 . This approach consists first of all to a rapid and important MB desorption (more than 91%) from fixed bed depth columns by low cost saline solutions (NaCl: 0.5 M). The issued solutions contained high MB concentrations (>3400 mg L −1 ) permitting a partial recovery of the dye as a solid phase with a purity of 93% that could be reused again in the industrial process. The second step concerns the treatment of the remaining dissolved MB in the desorbed solutions through anodic oxidation process by using bipolar Si/BDD (Boron Doped Diamond) electrodes. The presence of chlorides anions in the desorbed solutions enhances considerably their discoloration and organic carbon removal efficiencies and kinetics and significantly reduces the related consumed energy. The quality of the resulting treated wastewaters allows its possible reuse in the industrial process. Finally, five consecutive adsorption/desorption cycles experiments showed that ATOS could be reused several times for the MB adsorption without significant efficiencies decrease. All these results confirm the validity of our strategy aiming to turn dyes-loaded-lignocellulosic-biomasses from pollution source to values. Graphical abstract: Image 1 Highlights: Methylene blue desorption was studied in fixed bed column mode. Methylene blue desorption was governed by an ion exchange mechanism. Dye recovery was achieved with a high purity level of more than 92%. Biomass ability for reuse was confirmed after five successive regeneration cycles. High efficiency and low energy consumption when degrading MB by anodic oxidation.